Proceedings of the 2016 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2016
DOI: 10.1145/2851581.2892340
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation as an Interaction Mechanism for Deciding App Permissions

Abstract: On the Android platform, apps make use of personal data as part of their business model, trading location, contacts, photos and more for app use. Few people are particularly aware of the permission settings or make changes to them. We hypothesize that both the difficulty in checking permission settings for all apps on a device, along with the lack of flexibility in deciding what happens to one's data, makes the perceived cost to protect one's privacy too high. In this paper, we present the preliminary results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…In context-aware related technologies, it was found that majority of the medical apps under consideration had no privacy policy statements, despite their access to sensitive medical data Goh, 2015. A negotiated approach to setting app permissions Baarslag et al, 2016 and the rethinking of the design of consent mechanisms for ubiquitous computing were suggested Researchers have shown the benefit of plurality of epistemologies by demonstrating a difference in results as epistemological lens shift from positivist paradigm to the interpretive and lastly critical theory (Trauth & Howcroft, 2006;Trauth & Jessup, 2000). There is a growing number of critical research, albeit fewer in numbers relative to the former two epistemologies.…”
Section: Informed Decision Makingmentioning
confidence: 99%
“…In context-aware related technologies, it was found that majority of the medical apps under consideration had no privacy policy statements, despite their access to sensitive medical data Goh, 2015. A negotiated approach to setting app permissions Baarslag et al, 2016 and the rethinking of the design of consent mechanisms for ubiquitous computing were suggested Researchers have shown the benefit of plurality of epistemologies by demonstrating a difference in results as epistemological lens shift from positivist paradigm to the interpretive and lastly critical theory (Trauth & Howcroft, 2006;Trauth & Jessup, 2000). There is a growing number of critical research, albeit fewer in numbers relative to the former two epistemologies.…”
Section: Informed Decision Makingmentioning
confidence: 99%
“…Many disciplines must deal with the notion of privacy: anthropology, architecture, behavioural psychology, law, sociology, as well as computer science [4]. A taxonomy for privacy was developed by classifying privacy as being 'person-centred' and 'placecentred' (person-environment interactions': (1) private/public dichotomy, (2) an attribute of places and people, (3) as an interpersonal process, (4) a need, right and freedom, (5) an balancing act (balance between social interaction and the risks; risk/rewards as an economic decision) [5]. This privacy taxonomy would enable us to reveal data interactions and data actions and to understand what they really entail and their implications for privacy in IoT.…”
Section: Privacy and Privacy Protectionmentioning
confidence: 99%
“…In order to gives people informational power, consent has to be meaningful, i.e., consents have to be intelligible to, controllable by and visible to [(when, if)] users [2]. It is proposed that "apparency and semantic/pragmatic transparency" model could be adopted for data management ("apparency reflects how an activity is signalled.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to address the problems of security and privacy in this context have focussed on trust building [9], offering a balance of control over data [17], improving the efficacy of consent and permission processes [16,28,5,2], and raising awareness of the security risks of disclosing personal information [3,29]. Dupree et al [11] developed personas representing different types of attitude towards privacy and security concerns and behaviour, in an attempt to clarify the range of attitudes and approaches to managing data.…”
Section: Related Workmentioning
confidence: 99%